Analysis of value drivers behind CRM adoption projects in financial services industry - Rubinstein, Igor (My University, 2011)
This research is focused on deriving framework for the value thought for from the Customer Relationship Management system adopted by an enterprise operating in the financial services industry. It will analyze existing academic work to derive a conceptual value model, while applying secondary industry specific case studies provided by the CRM vendors to check the validity and commonality of these drivers. Furthermore this work locates the variances and correlation between value thought for from CRM system, scope of enterprise operations and size of the enterprise.